Housing tenure and educational opportunity in the Paris metropolitan area - Ramond, Quentin; Oberti, Marco (Housing Studies, 2020)
This paper examines the relationship between housing tenure and educational opportunities in the Paris metropolitan area. Using census microdata, we show that the middle classes face uneasy trade-offs between housing tenure and access to attractive educational resources. Living in high-quality school contexts is associated with renting, whereas access to homeownership mostly unfolds in poor-performing school areas. This tension is not observed for other social strata. Based on fieldwork conducted in Paris suburbs, we highlight the interweaving of middle-class housing and school choices. Some families may use the rental sector to live close to attractive schools. In mixed neighbourhoods, homeowners either choose the local school or opt for circumvention strategies. Because of the dramatic increase of housing prices, the interplay between housing tenure and the unequal geography of education is crucial to understand social stratification and social mobility patterns in large cities, particularly among the middle classes, as well as to improve public policies aimed at reducing housing and school inequalities.
Keywords: Housing tenure; education; inequality; middle classes; segregation